Taxation and Incentive in Mobilization: Comment - Schwartz, Harry S. (Quarterly Journal of Economics, 1952)
Journal Article Taxation and Incentive in Mobilization: Comment Get access Harry S. Schwartz Harry S. Schwartz San Francisco, California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 66, Issue 4, November 1952, Pages 600–605, https://doi.org/10.2307/1882110 Published: 01 November 1952